(untitled) - Giles, John R. (Cambridge [Cambridgeshire],New York, 1987)
Although the text is titled metric spaces, normed linear spaces are introduced immediately because this added structure is present in many examples and its recognition develops an interesting link with linear algebra
Keywords: Metric spaces,Normed linear spaces,Functional analysis,Không gian ma trận,Đại số tuyến tính